Analisis Keamanan Data Pribadi Pada Pengguna E-Commerce Shopee Terhadap Ancaman Data Pribadi - Tata Arya Cahyaaty; Indra Wijaya; Muhamad Dafin Al Dzky; Handika Gita Prasojo; Septian Hadi Prakoso (Journal of Informatic and Information Security, 2024)
This study discusses the protection of personal data on e-commerce platform Shopee, as the increasing use of e-commerce services makes data security issues increasingly important. With a qualitative descriptive approach, this study relied on literature analysis and secondary data to assess the implementation of security measures, such as data encryption and two-factor authentication (2FA). The results show that although Shopee has taken fairly good protective measures, there are still 28.26% of respondents who do not fully understand its security policies. The research also provides a number of recommendations to increase user awareness and strengthen security policies at Shopee as well as other e-commerce platforms.